Tensile Performance of Box-Sleeve Cold Formed Steel Connection - M F Mohamad Fikri; A F Kamaruddin (Journal of Structural Monitoring and Built Environment, 2026)
This study focused on the box-sleeve connection in the flange section of cold-formed steel C-sections. The research addressed the limited use of cold-formed steel compared to hot-rolled steel, emphasizing the need to study its tensile strength. The objective was to determine the tensile strength of box-sleeve connections with self-tapping screws and to analyze failure modes. Twelve samples were tested, divided into two thicknesses (0.75 mm and 1.00 mm), with each thickness having six samples. Three samples per thickness used two screws, while the other three used four screws. Tensile tests measured the ultimate load for each configuration. For the 0.75 mm thickness, the average ultimate load was 6–8 kN with two screws and 12–14 kN with four screws. For the 1.00 mm thickness, the average ultimate load was 12–14 kN with two screws and 20–25 kN with four screws. The results showed similar performance between 0.75 mm with four screws and 1.00 mm with two screws. The study concluded that both thickness and the number of screws significantly influence the tensile strength of the connection.